Tourism Impact on Economic Growth in Bali - Putri, Aulia Restu Ariyanto; Fadhila, Putri Ghina; Furqan, Alhilal (Archives of Business Research, 2023)
Tourism have made a significant contribution to the balance of trade and the development of the country’s overall economic policy which can be seen from the increasing number of international tourist visits to a particular destination country with various economic impacts occurred. This has led tourism being used as one of the strategies to reduce poverty and increased economic growth. Increased economic growth in the surrounding community can be seen from increased income, creating new jobs, diversifies the economy, adding new product, and contributing to the overall economic sector that is integrated to achieve an improved quality of life. This research focuses on economic growth that occurs due to tourism activities in Bali Province by considering the 5 (five) indicators of economic growth consisting of increasing revenues, diversifies economy, creates new job, generate additional income, and adds new products by conducting a documentation study in the span of the past 10 years.